Yerba buena eaudiobook A novel. - LaCour, Nina (Macmillan Audio, 2022)
"Full of sensory details, vivid characters, and moment after moment of gorgeously rendered ordinary life, this audiobook is a queer must-listen." - AudioFile This program is masterfully narrated by award-winning "Golden Voice" narrator Julia Whelan. Yerba Buena is the debut adult novel by the bestselling and award-winning YA author Nina LaCour, following two women on a star-crossed journey toward each other. A Most Anticipated Book ( Vogue , Harper's Bazaar , The Washington Post , Vulture , NBC News, Good Housekeeping , Parade, Electric Lit, BookRiot, Bustle, Goodreads, LGBTQ Reads, Autostraddle, Veranda Magazine , The Lesbian Review , and more) "A love story for our time."—Tara Conklin, New York Times bestselling author of The Last Romantics "This book is a precious thing."—Casey McQuiston, New York Times bestselling author of One Last Stop When Sara Foster runs away from home at sixteen, she leaves behind the girl she once was, capable of trust and intimacy. Years later, in Los Angeles, she is a sought-after bartender, renowned as much for her brilliant cocktails as for the mystery that clings to her. Across the city, Emilie Dubois is in a holding pattern, yearning for the beauty and community her Creole grandparents cultivated but unable to commit. On a whim, she takes a job arranging flowers at the glamorous restaurant Yerba Buena and embarks on an affair with the married owner. The morning Emilie and Sara first meet at Yerba Buena, their connection is immediate. But the damage both women carry, and the choices they have made, pulls them apart again and again. When Sara's old life catches up to her, upending everything she thought she wanted just as Emilie has finally gained her own sense of purpose, they must decide if their love is more powerful than their pasts. At once exquisite and expansive, astonishing in its humanity and heart, Yerba Buena is a love story for our time and a propulsive journey through the lives of two women trying to find somewhere, or someone, to call home. A Macmillan Audio production from Flatiron Books.